2016
DOI: 10.9734/ajea/2016/19823
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human Urine-compost Mixture on Some Soil Fertility Properties, Yield and Shelf-life of Tomato (Solanum lycopersicon)

Abstract: Human urine, especially if combined with composts, could be a good source of fertilizer for improving soil fertility and ultimately, crop production. Thus, the focus of this study was to evaluate the influence of human urine-compost mixture on post-harvest soil fertility quality, yield and shelflife of tomato (Solanum lycopersicon). The study had six fertilizer treatments: urine, compost, compost: urine -1:2, compost: urine -2:1, NPK 15-15-15 and the Control (no soil additive) laid in a Randomized Completely B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…and OMF mixtures (urea + SSP + urine + ORP) on dry shoot weight and fresh fruit weight respectively than inorganic fertilizer (urea + SSP). It could be observed that urine + ORP based fertilizer gave a better plant performance in terms of nutrient use efficiency and quality than urea + SSP, which supports the findings of [27] that human urine-compost combination 1:2 or 2:1 gave improved yield, shelf life and soil fertility than mineral fertilizers (NPK 15:15:15). He reported that human urine could be a good fertilizer for producing tomatoes and if combined with compost, effects are better.…”
Section: Discussionsupporting
confidence: 83%
“…and OMF mixtures (urea + SSP + urine + ORP) on dry shoot weight and fresh fruit weight respectively than inorganic fertilizer (urea + SSP). It could be observed that urine + ORP based fertilizer gave a better plant performance in terms of nutrient use efficiency and quality than urea + SSP, which supports the findings of [27] that human urine-compost combination 1:2 or 2:1 gave improved yield, shelf life and soil fertility than mineral fertilizers (NPK 15:15:15). He reported that human urine could be a good fertilizer for producing tomatoes and if combined with compost, effects are better.…”
Section: Discussionsupporting
confidence: 83%